Supervision degree of Palestinian governmental schools’ principals in tutorship new teachers from the teachers’ perspective - Alkaraki, Karam Sufian; Al-Sabbah, Suheir Sulieman (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree at which the governmental school principals practice their supervision in tutorship new teachers from the teacher’s own perspective, and to identify differences in the degree of practice of their supervisory duty according to (Teacher’s Gender, New teacher’s specialization, Principal’s specialization, qualification, and school educational stage). To achieve the goals of our study, the descriptive method was used, study population included Palestinian governmental schools’ teachers contained (1720) teachers, the sample contained (106) teachers males and females, they were chosen by convenience sampling method, the questionnaire was distributed electronically via google forms after ensuring its validity and reliability. The results revealed that the degree of supervision as a moderate degree in total at all fields. Also, it showed no significant differences in principal’s practice of supervision in relation to: principals’ specialization, new teacher’s specialization, and the qualification of teacher. There was significant difference in school educational stage for basic study stage on all fields, also it revealed significant difference in relation to teacher’s gender for Females in total and in all fields.